RYR1 Mutations, Exertional Myalgia and Rhabdomyolysis - J Gordon Millichap (Pediatric Neurology Briefs)
Investigators at Guy’s & St Thomas’ Hospital, London, UK, and other centers sequenced RYR1 in 39 unrelated families with rhabdomyolysis and/or exertional myalgia and identified 9 heterozygous RYR1 mutations in 14 families, 5 of them previously associated with malignant hyperthermia (MH).